Myths and Ideology in Customary Ritual of Ma’tammu Tedong for Life of Toraja People - Rita Tanduk; Nirwanto Maruf; Sallolo Suluh (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Customary ritual of rambu solo’ in Toraja is based on noble values of culture that influences life pattern of Toraja people. Current development has changed the way of life and thinking of Toraja people to customary ceremony. Basic understanding is needed in interpreting the ceremonies. This paper discusses the meaning of ritual text myth that is represented by buffalo meeting. Participant observation methods used with field notes, recording, and interview techniques completed the data collection. The data were analyzed interpretatively by semiotic approach. The ritual text of the buffalo meeting ceremony in rambu solo’ ceremony is a symbolic form, parallelism, and metaphor which also constructs the meaning of customary ritual myth. Through the ritual remarks on the seven types of buffalo in the ceremony of rambu solo’ indicating views, concepts, and motivations are used as guidelines for life for Toraja people. The result of the research shows that, (1) the customary ritual text of buffalo meeting is symbolic, parallelism, and metaphor characteristics that represent myth meaning, (2) customary ritual text of buffalo meeting is to construct myth and ideology about Toraja character value. The value of the characters is represented by the seven types of buffalo in the customary ritual ma'tammu tedong namely, (a) balian buffalo represented as a leader figure or role model; (b) bonga buffalo as torch in human life of Toraja; (c) pudu’ buffalo as guardians in maintaining the life of the Toraja; (d) todi’ buffalo as a unifier that strengthens kinship ties; (e) sokko’ buffalo describes a polite and humble person; (f) tekken langi’ buffalo as a safeguard that reconciles the Toraja over the conflict; (g) sambao’ buffalo as customary guardians for customary offenses. Those values indicate the existence of the relation between man and Almighty and man with others. Also, they strengthen the character of human life of the Toraja and nation character.